The Interrelations Between Different Causes of Dizziness: A Conceptual Framework for Understanding Vestibular Disorders. (September 2019) - Zhu, Richard T.; Van Rompaey, Vincent; Ward, Bryan K.; Van de Berg, Raymond; Van de Heyning, Paul; Sharon, Jeffrey D.
Background: According to population-based studies that estimate disease prevalence, the majority of patients evaluated at dizziness clinics receive a single vestibular diagnosis. However, accumulating literature supports the notion that different vestibular disorders are interrelated and often underdiagnosed. Objective: Given the complexity and richness of these interrelations, we propose that a more inclusive conceptual framework to vestibular diagnostics that explicitly acknowledges this web of association will better inform vestibular differential diagnosis. Methods: A narrative review was performed using PubMed database. Articles were included if they defined a cohort of patients, who were given specific vestibular diagnosis. The interrelations among vestibular disorders were analyzed and placed within a conceptual framework. Results: The frequency of patients currently receiving multiple vestibular diagnoses in dizziness clinic is approximately 3.7% (1263/33 968 patients). The most common vestibular diagnoses encountered in the dizziness clinic include benign paroxysmal positional vertigo (BPPV), vestibular migraine, vestibular neuritis, and Ménière's disease. Conclusions: A review of the literature demonstrates an intricate web of interconnections among different vestibular disorders such as BPPV, vestibular migraine, Ménière's disease, vestibular neuritis, bilateral vestibulopathy, superior canal dehiscence syndrome, persistent postural perceptual dizziness, anxiety, head trauma, and aging, among others.